1988
DOI: 10.3354/meps047055
|View full text |Cite
|
Sign up to set email alerts
|

Respiration, ventilation and circulation under hypoxia in the glacial relict Saduria (Mesidotea) entomon

Abstract: The glacial relict Saduria (Mesidotea) entornon (L.) (Crustacea: Isopoda) lives buried in sandy/muddy bottoms in the Baltic. During hypoxia Saduria remains buried until oxygen tension (P,Oz) has decreased to < 5 Torr (8°C; 7 % S). Respiration rate (MO2) for buried Saduria was lower than for other crustaceans of similar size. Saduria is able to maintain a stable MO2 with decreasing P,Oz down to < 5 to 10 Torr, i.e. in practice over the entire P , 0 2 range. After exposure to severe hypoxia for many hours a resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…In Nephrops norvegicus it was shown that not only anoxia (through aerial exposure) but also the hypoxic conditions (10Á30% O 2 saturation) in the bottom water of certain fishing grounds cause significant glycogen depletion, thus indicating anaerobic fermentation (Baden et al 1994). Interestingly, some animals like Saduria entomon (Linnaeus, 1758) can also maintain their oxygen demand (aerobic ATP production) for some time by adaptation of ventilation and haemolymph circulation frequencies, before ultimately switching to anaerobic pathways (Hagerman & Szaniawska 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In Nephrops norvegicus it was shown that not only anoxia (through aerial exposure) but also the hypoxic conditions (10Á30% O 2 saturation) in the bottom water of certain fishing grounds cause significant glycogen depletion, thus indicating anaerobic fermentation (Baden et al 1994). Interestingly, some animals like Saduria entomon (Linnaeus, 1758) can also maintain their oxygen demand (aerobic ATP production) for some time by adaptation of ventilation and haemolymph circulation frequencies, before ultimately switching to anaerobic pathways (Hagerman & Szaniawska 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Leonardsson et al 1987, Hagerman & Szaniawska 1988, 1990, 1991, 1992, Haahtela 1990, Vismann 1991. These studies have revealed S. entomon to be a most adaptable species with an exceptional tolerance of anoxia and hydrogen sulphide concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the respiratory responses of Saduria entomon have been studied intensively (Hagerman & Szaniawska 1988, 1990, 1991, 1992, the origin and fate of the nitrogenous end products of this species are not well known. The purpose of the present study was thus to investigate ammonia efflux rates and haemolymph nitrogen compounds under anoxia in S. entomon.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic metabolism, starting when oxygen extraction can no longer be maintained, results in only a slight increase in haemolymph lactate with time in Saduria entomon (Hagerman & Szaniawska 1988). This is surprising as lactate is normally the only endproduct of anaerobic glycolysis in crustaceans (de Zwaan & Putzer 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It is a very eurybiontic species showing extremely high tolerances to anoxia and salinity variations, whilst temperatures above 12 to 15 "C are lethal (Hagerman & Szaniawska unpubl.). The metabolic rate is low with a high efficiency of oxygen extraction making it possible to maintain a stable MOz respiratory rate down to 5 or 10 Torr (Hagerman & Szaniawska 1988). Even at low p,02 S. entomon seems to be active, undertaking digging and feeding.…”
Section: Introductionmentioning
confidence: 99%